Essential oils from herbs against foodborne pathogens in chicken sausage - Barbosa, Lidiane Nunes [UNESP]; Probst, Isabella Silva [UNESP]; Murbach Teles Andrade, Bruna Fernanda [UNESP]; Bergamo Alves, Fernanda Cristina [UNESP]; Albano, Mariana [UNESP]; Mores Rall, Vera Lucia [UNESP]; Fernandes Junior, Ary [UNESP] (Japan Oil Chemists Soc, 2015)
Consumption of chicken meat and its products, especially sausage, have increased in recent years. However, this product is susceptible to microbial contamination during manufacturing, which compromises its shelf life. The flavoring and preservative activities of essential oils (EO) have been recognized and the application of these antimicrobial agents as natural active compounds in food preservation has shown promise. The aim of this study was to evaluate the effect of Ocimum basilicum and Origanum vulgare EO on Listeria monocytogenes and Salmonella Enteritidis strains in artificially inoculated samples of fresh chicken sausage. First, the minimal inhibitory concentration (MIC) of EO in vitro was determined. The sausage was prepared and kept at +/- 4 degrees C; then, the inoculation of individual bacteria was carried out. EO were added at 0.3%, 1.0% and 1.5%v/w. After 0, 5, and 24 hours, the most probable number method (MPN) was performed. Transmission electron microscopy (TEM) was used to view the damage caused by these EO on bacterial morphology and/or structure. Only the 1.5% concentration was effective in reducing L. monocytogenes. 0.3% of O. vulgare EO was able to reduce the MPN/g of Salmonella Enteritidis (2 log) after 5 hours trials. O. basilicum EO showed no effect on Salmonella after 5 hours, but decreased by 2 log after 24 hours. O. vulgare EO at 1% gave a greater reduction of S. Enteritidis at 5 hours, increasing or maintaining this effect after 24 hours. The results confirmed the potential benefits of use EO in control of foodborne pathogens.
Keywords: Ocimum basilicum; Origanum vulgare; Salmonella enteritidis; Listeria monocytogenes; Preservative